2020
DOI: 10.20517/2574-1225.2020.90
|View full text |Cite
|
Sign up to set email alerts
|

Robotic liver surgery: literature review and current evidence

Abstract: In the field of minimally invasive surgery, robotic surgery (RS) was introduced to overcome drawbacks in laparoscopic surgery. However, its clinical application in hepatobiliary surgery is not yet standardized. This review analyzed the results of RS to clarify the benefits of robotic liver surgery in comparison with standard laparoscopy. Among 112 publications found in the literature, the 72 most relevant were selected and the following data were extracted: patients characteristics, operative procedures, histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 63 publications
(145 reference statements)
0
11
0
Order By: Relevance
“…HCC is the predominant malignancy for which a robotic approach has been utilised, with 40% of the cases published in the literature indicating this as the underlying indication [22]. Three studies have examined the longer term oncological outcomes following robotic hepatectomy in this cohort and found the oncological outcomes to be comparable.…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
See 2 more Smart Citations
“…HCC is the predominant malignancy for which a robotic approach has been utilised, with 40% of the cases published in the literature indicating this as the underlying indication [22]. Three studies have examined the longer term oncological outcomes following robotic hepatectomy in this cohort and found the oncological outcomes to be comparable.…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
“…A recent review of outcomes from 584 major robotic liver resections demonstrated acceptable blood loss, operation time, R0 resection rate, length of hospital stay and post op morbidity. When directly compared to laparoscopy, robotic major hepatectomies demonstrated significantly improved rates of post-operative critical care admission, 90 day re-admission rate and a similar length of stay and complication rate [22]. The robotic approach has also been shown to be feasible for simultaneous resection of a colorectal primary malignancy and the associated liver metastasis.…”
Section: Current Evidence 31 Major Resectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Robot-assisted hepatic surgery has rapidly become a widely used modality for liver surgery and is being used throughout the world to treat a wide spectrum of hepatic lesions. This advanced technique was introduced to overcome some of the limitations associated with laparoscopic liver surgery, but many of the techniques are not yet standardized [ 57 ]. The purported advantages of robot-assisted hepatic surgery include increased dexterity and enhanced suturing ability, which is in part due to a magnified three-dimensional view of the operative field, hand tremor filtration, and articulating instruments with seven degrees of freedom [ 57 ].…”
Section: Robot-assisted Hepatic Surgerymentioning
confidence: 99%
“…This advanced technique was introduced to overcome some of the limitations associated with laparoscopic liver surgery, but many of the techniques are not yet standardized [ 57 ]. The purported advantages of robot-assisted hepatic surgery include increased dexterity and enhanced suturing ability, which is in part due to a magnified three-dimensional view of the operative field, hand tremor filtration, and articulating instruments with seven degrees of freedom [ 57 ]. Furthermore, robot-assisted hepatic surgery is felt to significantly reduce surgeon fatigue, with improved performance during long operations.…”
Section: Robot-assisted Hepatic Surgerymentioning
confidence: 99%